Mechanisms of Macrolide Resistance in Clinical Group B Streptococci Isolated in France - Fitoussi, Frederic (American Society for Microbiology, 2001)
Macrolide susceptibility was investigated in clinical group B streptococci obtained from neonates or pregnant women in 2000 in France. Of 490 consecutive isolates, 18% were resistant to erythromycin. The erm(B), erm(A) subclass erm(TR), and mef(A) genes were harbored by 47, 45, and 6% of these strains, respectively. Two isolates did not harbor erm or mef genes.